The Turks and the Ottoman Empire in South Slavonic prophecies - Dziadul, Paweł (Balcanica Posnaniensia. Acta et studia, 2014)
The main aim of this work is the presentation and analysis of anti-turkish and anti-Islamic ideas found in the South Slavonic prophecies. Prophetic and apocalyptic literature developed in two connected directions in the Ottoman period among the Orthodox Slavs in the Balkans. On the one hand, old prophetic and apocalyptic material (such as the <span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Revelation of Pseudo-Methodius, prophecies of Leo the Wise, the apocryphal <span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Visions of Daniel) was actualized according to new historical-political circumstances. On the other hand, new anti-turkish prophecies were created in that period. However, marginal glosses, interpolations or compilations were often used in that process. Anti-Turkish and anti-Islamic ideas focused mainly on the future Ottoman doom and the image of the legendary emperor who was supposed to defeat the “Ishmaelites”.